(untitled) (Journal of Medical & Health Sciences Review, 2023)
The human gut microbiome plays a pivotal role in maintaining homeostasis and influencing various physiological processes. This scholarly article reviews the current state of knowledge regarding the gut microbiome and its implications for human health and disease. We explore the intricate relationship between the gut microbiota and the host, emphasizing its impact on immune function, metabolism, and disease susceptibility. Additionally, we discuss recent advancements in microbiome research and their potential applications in personalized medicine and therapeutic interventions. Keywords: Gut microbiome, Microbiota, Health, Disease, Immune function, Metabolism, Personalized medicine, Therapeutic interventions.